Serology in COVID-19: Comparison of Two Methods † - Moniuszko-Malinowska, Anna (Int J Environ Res Public Health, 2021)
Background: The aim of our study was to examine the performance of two assays in detecting SARS-CoV-2 antibodies. Methods: A total of 127 COVID-19 disease contacts from the Infectious Diseases Department were included. Two serological tests were used: SARS-CoV-2 IgG CMIA on the Alinity system (Abbott) and LIAISON(®) SARS-CoV-2 S1/S2 IgG CLIA (DiaSorin). Results: The assays exhibited a 96.85% (123/127 patients) test result agreement. In two cases, the positive results obtained by SARS-CoV-2 IgG CMIA on the Alinity system (Abbott) were negative based on the LIAISON(®) SARS-CoV-2 S1/S2 IgG CLIA (DiaSorin) test, and in two cases, negative results from the LIAISON(®) SARS-CoV-2 S1/S2 IgG CLIA (DiaSorin) test were positive with the SARS-CoV-2 IgG CMIA on the Alinity system (Abbott). Conclusions: Based on the results of our study, we conclude that in population medicine, the assessments of anti-SARS-CoV-2 antibodies after exposure to SARS-CoV-2 virus based on spike protein or nucleocapsid protein show comparable effectiveness.